PENGARUH TAX PLANNING, PROFITABILITAS, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN BOD DIVERSITY SEBAGAI VARIABEL MODERASI - Nashar, Muhammad; Tartilla, Nilda; Wahyuni Rossa Putri,, Wulan (Solusi, 2022)
This study aims to examine and analyze the effect of tax planning, profitability, and liquidity on firm value with board diversity as a moderating variable. The population in this study is manufacturing companies in the consumer goods industry sector listed on the IDX in 2014-2019. The sampling method used purposive sampling with a total final sample of 60 companies. The analytical technique used is Moderating Regression Analysis (MRA). The results of the analysis show that the independent variable, namely profitability, has an influence on firm value. Meanwhile, tax planning and liquidity have no effect on firm value. And board diversity cannot moderate the effect of tax planning, profitability, and liquidity on firm value.Keywords: tax planning, profitability, liquidity, board diversity, firm value